Annuals and perennials : a gardener's encyclopedia - Bryant, Geoff; Rodd, Tony (Firefly Books, 2011)
With thousands of species to select from, how do you find the best plants for your garden? This guide provides a comprehensive selection table with characteristics, growth habits, and needs of each plant, as well as information on subspecies, hybrids, and cultivars. You're certain to find the right plant every time!